Prevention and Treatment of Postoperative Infections after Sinus Elevation Surgery: Clinical Consensus and Recommendations. (9th August 2012) - Testori, Tiziano; Drago, Lorenzo; Wallace, Steven S.; Capelli, Matteo; Galli, Fabio; Zuffetti, Francesco; Parenti, Andrea; Deflorian, Matteo; Fumagalli, Luca; Weinstein, Roberto L.; Maiorana, Carlo; Di Stefano, Danilo; et al.
Abstract : Introduction . Maxillary sinus surgery is a reliable and predictable treatment option for the prosthetic rehabilitation of the atrophic maxilla. Nevertheless, these interventions are not riskless of postoperative complications with respect to implant positioning in pristine bone. Aim . The aim of this paper is to report the results of a clinical consensus of experts (periodontists, implantologists, maxillofacial surgeons, ENT, and microbiology specialists) on several clinical questions and to give clinical recommendations on how to prevent, diagnose, and treat postoperative infections. Materials and Methods . A panel of experts in different fields of dentistry and medicine, after having reviewed the available literature on the topic and taking into account their long-standing clinical experience, gave their response to a series of clinical questions and reached a consensus. Results and Conclusion . The incidence of postop infections is relatively low (2%–5.6%). A multidisciplinary approach is advisable. A list of clinical recommendation are given.